Kinetics and Mechanism of Thermal Decomposition of γ-Irradiated Manganese Oxalate - Suryanarayanan, M.P. (Asian Journal of Chemistry, 2010)
The thermal decomposition of γ-irradiated manganese oxalate was studied by dynamic thermogravimetry. Kinetic parameters were calculated and the values were compared with those of unirradiated sample. The E, Z and ΔS* values decreased, reached a minumum and increased with increasing doses of radiation. The effect of γ-irradiation on the mechanism of decomposition was also studied. The mechanism is found to be changing on irradiation.